(untitled) (MAUSAM, 1987)
In this study remote sensing technique has been adopted to monitor changes in vegetation cover during the crop growing season and assess the drought conditions. Normalized difference of Landsat Multispectral Scanner (MSS) near Infrared (NIR) band (0.8-1.1 um) and red band (0.6-0.7 um) spectral data has been found useful to monitor the change in crop and vegetation cover (green cover) due to drought. The technique was tired for 1982 drought In parts of Karnataka State 54 percent reduction in green cover.